Coronavirus infection in patients with HIV infection, features of the course - E. V. Stepanova; O. N. Leonova; A. S. Shelomov; T. N. Vinogradova (Журнал инфектологии, 2021)
Purpose. Analyze and identify the features of the course of the new coronavirus infection (COVID-19) in HIV-infected patients.Materials and methods. An analysis of the course of coronavirus infection (COVID-19) was carried out in 16 patients with HIV infection who were hospitalized at the St. Petersburg State Budgetary Healthcare Institution Center for the Prevention and Control of AIDS and Infectious Diseases from April to October 2020. All patients underwent a study of biological material from the oropharynx and nasopharynx for COVID-19 and diagnosed based on a positive PCR result.Results. In HIV-infected patients with diagnosed coronavirus infection caused by COVID-19, signs of progression of HIV infection, clinical, immunological, virological (75%), opportunistic diseases and comorbidities (chronic viral hepatitis in the cirrhotic decompensated stage, cardiovascular diseases and others) (94%). A small sample of patients did not allow to determine with reliable accuracy the mutual influence of existing diseases and pathologies, but, of course, multiple comorbid pathologies play a role in the development of severe conditions and unfavorable outcomes. A clinical case is presented.Conclusion. The provoking factors have been identified that play a role in the development of infection and more severe forms of coronavirus infection caused by COVID-19 in HIV-infected patients (injecting drug use, alcohol abuse, late stage of HIV infection (4B, 4C) and progression of earlier stages (4A ), a low number of CD4 lymphocytes (less than 200 cells / μl), multiple comorbid pathology (HIV infection, opportunistic diseases, comorbidities, especially chronic liver damage in the stage of decompensated cirrhosis), absence, interrupted antiretroviral therapy, multiple changes of regimens, absence prevention of opportunistic diseases). A patient with HIV infection at ART. 4B with multiple comorbidity, the possibility of long-term persistence of the COVID-19 virus coronavirus with positive and negative results for more than 2 months and later development of lung damage caused by COVID-19 was established.